KAJIAN EFEKTIVITAS PEMANFAATAN INSENTIF PAJAK OLEH USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI MASA PANDEMI COVID-19 - Dewi Noor Fatikhah Rokhimakhumullah (Journal Publicuho, 2021)
The COVID-19 pandemic has had a high impact on the business and economy sector in Indonesia. To respond to this, the government has issued various policies, especially for MSMEs. Tax incentives for MSMEs issued by the government can be utilized by taxpayers until June 2021. This research aims to see the effectiveness of the use of tax incentives by mapping the factors that affect MSME taxpayer compliance and the determinants of MSME business success during the crisis due to the pandemic. This study uses a literature study approach with a descriptive qualitative method. The effectiveness of the use of tax incentives during this pandemic can show the level of compliance of MSME taxpayers and affect the sustainability of MSME businesses. Taxpayer compliance with the use of incentives is seen from the socialization of taxation, tax rates, understanding of taxation, and the perception of tax convenience provided by the government in the context of handling the impact of the pandemic, which shows that the response of MSMEs is very good in the first quarter of 2021. It is also seen from the perspective of MSME business continuity. The financial impact caused by this pandemic has caused MSMEs to be unable to carry out their tax obligations so that these tax incentives can provide relief and convenience for them MSME actors to carry out their tax obligations.